An unusual condition during internal jugular vein catheterisation: vertebral artery catheterisation - Korkmaz, Ozge (Cardiovasc J Afr, 2016)
Vertebral artery cannulation is an unusual complication during internal jugular vein cannulation. We report a case of vertebral artery cannulation, which occurred during an attempt to cannulate the right internal jugular vein, and we discuss the management of such a rare complication.